The Correlation Between The Use Of Face Moisturizers On The Incidence Of Acne Vulgaris Due To Masks - Ashauma Aksanul Muttaqin; Ari Budi Himawan; Lusiana Batubara; Widyawati Widyawati (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: Acne vulgaris or widely known as acne, is a skin disease in the form of inflammation of the pilosebaceous unit characterized by the appearance of comedones, papules, pustules, and nodules. Due to the Coronavirus disease 2019 (COVID-19) pandemic, masks have become personal protective equipment (PPEs), commonly used by health workers and the general public. The combination of friction, repeated pressure, sweat, or stress on the skin from wearing the mask causes acne or an exacerbation of existing acne. Meanwhile, the use of facial moisturizer can maintain skin moisture and help the repair process of the structure of the skin barrier.Objective: This study aims to determine the relationship between the use of facial moisturizers and the incidence of acne vulgaris due to masks.Methods: This study is an analytical observational study with a cross-sectional design. The subjects in this study amounted to 44 people who were nurses at the Diponegoro National Hospital who had approved the informed consent form, filled out a complete questionnaire, and included the research criteria. The research sample was selected using purposive sampling. The diagnosis of acne vulgaris was made by doctor-in-charge based on the subject's face photo. The statistical test used is Fischer's Exact Test.Results: Based on data analysis using Fischer's Exact Test, the results showed no significant relationship between the use of facial moisturizers and the incidence of acne vulgaris due to masks with a p-value = 0.722 (p>0.05).Conclusion: There is no relationship between the use of facial moisturizers with the incidence of acne vulgaris due to masks.